Design and application of content distribution engine for the nuclear power enterprise - Peng WANG; Hongbing TU; Yunfu WANG (Dianxin kexue)
Content distribution is an important business of nuclear power enterprises,and is responsible for transferring structured/unstructured content media between companies,departments,project groups and other levels.The complexity of the content media structure,the participation in the distribution hierarchy,and the variety of distribution business scenarios pose great challenges on the design of the distribution engine.After sorting out the company’s distribution business,a dynamically configurable content distribution engine was designed,which supported business logic configuration and reduced frequent engine changes caused by changes in distribution business.Combined with the database trigger technology,a pre-engine content crawling mechanism was designed,which could greatly reduce the crawling time complexity and space complexity of the content to be distributed,and ensure the immediacy of the task.